Effect of health expenditure on maternal and child health in Nigeria - Abiola Abosede Solanke; Olufisayo Olayinka Akinlo; Olumuyiwa Tolulope Apanisile; Rafiu Oyesola Salawu (Accounting, 2025)
The study investigated how public funds promote maternal and child health indicators in Nigeria from 1978 to 2023. The study adopted a generalized method of moments (GMM) in the analysis. The empirical results revealed that health expenditure positively and significantly impacted maternal and child health in Nigeria. The study concluded and recommended that the government should focus on increasing allocation to the health sector year in and year out to improve maternal and child health rather than relying on international funding, as an increase in health expenditure reduces the maternal and child mortality rate in Nigeria.